iCMR – BUILD HIGH IMPACT RESEARCH COLLABORATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 The International Conference on Multidisciplinary Research (iCMR 2015) has succeeded in attracting more than 180 paper presentations by participants from various countries around the world.